Application of a ternary phase diagram to the liquid-liquid extraction of ethanoic acid using ethyl ethanoate - Madeira, Aline Amaral (Eclética Química, 2019)
This article describes the liquid-liquid equilibrium of the extraction process of ethanoic acid (C2H4O2) in aqueous phase using ethyl ethanoate as the solvent. The liquid-liquid extraction was modeled by the construction of a ternary phase diagram for the water/ethanoic acid/ethyl ethanoate system using the Origin software. The equilibrium data were experimentally obtained by titration at room temperature (298.15 K) and atmospheric pressure (101325 Pa) using four mixtures of water, ethanoic acid, and ethyl ethanoate. The determination of the composition of the extract and residue portions in the equilibrium of each mixture by of the tie-lines method allowed to examine the percentages of liquid-liquid extraction achieved. The distribution coefficients and separation factors calculated, made it possible an evaluation of the distribution and of the mutual solubility of the solute in the aqueous and organic phases. The results showed a good performance of ethyl ethanoate in the extraction of ethanoic acid for concentrations of solute until 16% of the feed.